DUALISME KEDUDUKAN DAN TANGGUNG JAWAB NOTARIS DALAM TATANAN SISTEM HUKUM NASIONAL - Isis Ikhwansyah; Indra Prayitno (Faculty of Sharia and Law, Sunan Gunung Djati Islamic State University of Bandung, 2019)
Abstract: Government policies related to notary institutions from the beginning of their emergence until now, it has not been able to provide certainty related to the independence of the Notary Position in the order of the National legal system. Is it purely as a public official like a state official, or is the legal profession, and or is a Public Official combined with a legal profession position because it influences his responsibilities. This study aims to find out how the position and responsibilities of a notary in the current national legal system, this research method uses a juridical normative approach method that is analyzed descriptively analytically on the basis of data that is processed in a juridical way qualitatively, logically and systematically. From the results of the study note that the Notary has a position as a